PERTANGGUNGJAWABAN PIDANA TERHADAP PEMBERIAN FASILITAS PEMBIAYAAN MODAL KERJA FIKTIF OLEH BANK MENGENAI PROSEDUR DOKUMEN DAN JAMINAN (Studi di Bank Muamalat Indonesia Cabang Kota Medan) - Nasution, Rahmat Surkhalid; Siagian, Abdul Hakim; Miroharjo, Didik (Jurnal Ilmiah Advokasi, 2021)
The basis of lending or financing by banks to debtor customers is trust by implementing the principle of prudence by applying the principle of knowing the customer. Documents and credit guarantees approved and received by the bank will then have several functions and one of them is to secure the repayment of credit if the borrower injured the promise. Fictitious crimes in the provision of credit facilities or working capital financing actually refer to various forgeries. There are 3 (three) types of forgery, namely making fake letters, falsifying letters, intellectual forgery. The criminal liability of banks contained in Law No. 10 of 1998 concerning Amendment to Law No. 7 of 1992 on Banking and Law No. 21 of 2008 on Syariah Banking is cumulative criminalization meaning that in addition to being sentenced to prison or also sentenced simultaneously in accordance with its mistakes.Keywords: Bank, Financing, Fictitious and Criminal LiabilityÂ